Somatostatin receptor based hybrid imaging in sarcoidosis - Riemer H. J. A. Slart; Klaas-Pieter Koopmans; Peter Paul van Geel; Henk Kramer; Harry J. M. Groen; C. Tji-Joong Gan; Niek H. J. Prakken; Andor W. J. M. Glaudemans; George D. Nossent (European Journal of Hybrid Imaging, 2017)
Abstract Several diagnostic imaging methodologies are available for the clinical evaluation of sarcoidosis, but all have their limitations. FDG PET/CT is frequently used, but this technique does not provide optimal results in all cases. Novel radiopharmaceuticals aimed at other disease targets may be helpful, particularly in cardiac sarcoidosis when FDG PET/CT has a low diagnostic accuracy, due to difficulties in preparing the patients who should use a specific diet combined with prolonged fasting. 68Ga-labeled somatostatin based receptor hybrid imaging is a potential alternative to FDG PET/CT. This short communication provides a rapid overview of initial findings concerning the application of 68Ga-labeled somatostatin based receptor hybrid imaging in the diagnosis of (cardiac) sarcoidosis activity.